UTILIZING RAMADAN TRADITIONS TO ENHANCE ENGLISH SPEAKING SKILLS IN AN ENGLISH COURSE - Nadia, Hikmatun; Amalia, Taranindya Zulhi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Speaking skills are one of the important competencies in mastering English, but many students still have difficulty expressing ideas orally, especially in the context of relevant daily life, such as Ramadan traditions. Lack of motivation and student involvement in the learning process also worsens their speaking skills. This study aims to determine how Ramadan traditions can be used as a contextual approach to improve English speaking skills at Rumah Kita English Course. The focus of the study was directed at integrating activities related to Ramadan traditions into the language learning process. This study used a qualitative approach with data collection techniques in the form of observation, interviews, and documentation of Ramadan activities such as discussions on sahur and breaking fast menus, as well as sharing fasting experiences in English. The results showed that the implementation of Ramadan tradition-based activities was able to increase students' self-confidence, enrich vocabulary, and encourage more active verbal interaction in English. In addition, students showed higher interest and involvement during the learning process. The conclusion of this study is that the integration of local cultural values, especially Ramadan traditions, in foreign language learning can create a more relevant, enjoyable, and meaningful learning atmosphere. This approach not only strengthens students' speaking skills but also fosters an appreciation of culture in the language learning process. ABSTRAKKeterampilan berbicara merupakan salah satu kompetensi penting dalam penguasaan bahasa Inggris, namun masih banyak siswa yang mengalami kesulitan dalam mengungkapkan ide secara lisan, terutama dalam konteks kehidupan sehari-hari yang relevan, seperti tradisi Ramadan. Kurangnya motivasi dan keterlibatan siswa dalam proses pembelajaran turut memperburuk kemampuan berbicara mereka. Penelitian ini bertujuan untuk mengetahui bagaimana tradisi Ramadan dapat digunakan sebagai pendekatan kontekstual untuk meningkatkan keterampilan berbicara bahasa Inggris di Rumah Kita English Course. Fokus penelitian diarahkan pada integrasi kegiatan-kegiatan yang berkaitan dengan tradisi Ramadan ke dalam proses pembelajaran bahasa. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi kegiatan Ramadan seperti diskusi menu sahur dan buka puasa, serta berbagi pengalaman puasa dalam bahasa Inggris. Hasil penelitian menunjukkan bahwa penerapan kegiatan berbasis tradisi Ramadan mampu meningkatkan kepercayaan diri siswa, memperkaya kosakata, serta mendorong interaksi verbal yang lebih aktif dalam bahasa Inggris. Selain itu, siswa menunjukkan minat dan keterlibatan yang lebih tinggi selama proses pembelajaran berlangsung. Simpulan dari penelitian ini adalah bahwa integrasi nilai-nilai budaya lokal, khususnya tradisi Ramadan, dalam pembelajaran bahasa asing dapat menciptakan suasana belajar yang lebih relevan, menyenangkan, dan bermakna. Pendekatan ini tidak hanya memperkuat keterampilan berbicara siswa, tetapi juga menumbuhkan apresiasi terhadap budaya dalam proses pembelajaran bahasa.